Does revenue sharing reduce regional disparity?. Issue 21 (3rd May 2022) - Han, Xin; Han, Yutao; Wan, Xi
ABSTRACT: This article investigates the role of tax revenue sharing on regional development disparity. We show that competition in taxes and infrastructure widens the development gap among jurisdictions under both simultaneous and sequential games. Particularly, the results suggest that the development disparity increases with the degree of tax sharing under sequential game. The reason is that the fiscal transfers received by the lagging jurisdiction overcompensate for the loss of capital outflow and thus discourage the lagging from investing in public infrastructure. However, revenue sharing has no effect on the development disparity when simultaneous game is considered.